PENERAPAN MODEL PEMBELAJARAN TIPE SNOWBALL THROWING DENGAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR SEJARAH (PENELITIAN TINDAKAN KELAS DI KELAS XI IIS 4 SMA NEGERI 6 SURAKARTA PADA SEMESTER GENAP TAHUN AJARAN 2015/2016) - Yoshisa, Hanako Sukma; Herimanto, Herimanto; Suryani, Nunuk (Candi, 2017)
The aims of this research is to enhance the students? activeness and learning outcomes of students in class XI IIS 4 SMA Negeri 6 Surakarta by implementing the cooperative learning modelssuch as snowball throwing model in history subject.This research is a class behaviour research (CBR). The research was conducted in two cycles, with each cycle consist with a plan, action, observation, and reflection. The subjects were 30 students of class XI IIS 4 SMA Negeri 6 Surakarta. Source of data was derived from the teacher, the students and the learning process. Data collection techniques were implemented by conducting tests, observations, interviews, documentation, and questionnaires. Testing the data validity was by using triangulation techniques. Data analysis was conducted by using comparative descriptive analysis techniques. The research model used was the spiral model (Planning, Acting, Observing and Reflecting).The results showed that the teacher could be categorized as be able to teach well in the learning process, so that the learning process ran well. The ability of teachers to teach in pre-cycle was 62,50% which increased to 79,50% in the first cycle and 85,71% in the second cycle. The implementation of snowball throwing could enhance the students? activeness and learning outcomes of studying history subject of class XI IIS  4 in pre-cycle to the first cycle and from cycle I to cycle II. The students? activeness in pre-cycle was 50,15% which increased to 60,17% in the first cycle and 82.10% in the second cycle. The completeness ofstudents? learning outcomes in pre-cycle was 40,40% which increased to 62,80% in the first cycle and successfully developed to 82,00% in the second cycle.Based on the results of research and discussion, it can be drawn the conclusion that the snowball throwingenhance the students? activeness and learning outcomes of class XI IIS 4 SMA Negeri 6 Surakarta.